EMOTIONAL CONTEXT AND ITS COMMUNICATIVE FEATURES (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
In recent years, the emotional context and its role in the communication process have been deeply analyzed. Within the scope of the topic, how emotions function as signaling tools in communication and how they are expressed through verbal and nonverbal cues are examined. The article also includes insights into the dependence of emotional context on cultural, social, and personal factors, as well as its importance for effective communication. The research findings serve to enhance communication efficiency by understanding and managing emotional components.